Fexuprazan safeguards the esophagus from hydrochloric acid-induced damage by suppressing NLRP1/Caspase-1/GSDMD pyroptotic pathway - Kim, Seo Yeon; Yoon, Jung-Ho; Jung, Da Hyun; Kim, Ga Hee; Kim, Chul Hoon; Lee, Sang Kil (Frontiers in Immunology, 2024)
IntroductionProton pump inhibitors (PPIs) and potassium-competitive acid blockers (P-CABs) are widely used to manage gastric acid-related disorders by inhibiting hydrochloric acid (HCl) secretion from parietal cells in the stomach. Although PPIs are known to have anti-inflammatory properties beyond their role in inhibiting gastric acid secretion, research on P-CABs is lacking. In this study, we aimed to investigate whether all available P-CABs exhibit anti-inflammatory effects in gastroesophageal reflux-induced esophagitis and to elucidate the underlying mechanisms.MethodsHet-1A cells, normal esophageal epithelial cells, were treated with HCl (pH 4) for 30 min. Esomeprazole, a representative PPI, and three currently marketed P-CABs (vonoprazan, tegoprazan, and fexuprazan) were used for pretreatment. Total RNA sequencing was performed using Het-1A cells pretreated with 1% DMSO or fexuprazan, followed by exposure to HCl. Pyroptosis was measured using lactate dehydrogenase (LDH) release and Annexin V-FITC/PI staining. Western blotting, qRT-PCR, and ELISA were used to determine the expression of the related genes.ResultsPretreatment with esomeprazole, vonoprazan, tegoprazan, and fexuprazan significantly inhibited the HCl-induced pro-inflammatory cytokines, including IL-6, IL-8, IL-1β, and TNF-α. Fexuprazan and vonoprazan significantly attenuated the HCl-induced pyroptosis rate, as assessed by elevated LDH release and Annexin V-FITC/PI staining, whereas esomeprazole and tegoprazan did not. RNA sequencing revealed that NOD-like receptor (NLR) family pyrin domain-containing 1 (NLRP1) was significantly reduced in Het-1A cells pretreated with fexuprazan compared to those treated with DMSO. Fexuprazan and vonoprazan markedly reduced the HCl-induced transcriptional and translational expression of genes involved in the pyroptosis pathway, including NLRP1, Caspase-1, gasdermin D, and IL-1β. Notably, fexuprazan reduced the HCl-induced increase in pyroptosis and IL-1β using siRNA, even in the presence of NLRP1 knockdown. Fexuprazan, tested on inflammatory THP-1 macrophage cells, significantly reduced NLRP1 expression and inhibited lipopolysaccharide-induced pyroptosis.ConclusionOur findings reveal that all p-CABs exhibit anti-inflammatory properties, while fexuprazan inhibits inflammation and pyroptosis of esophageal cells caused by the gastric acid. Therefore, it is presumed to have additional benefits in gastroesophageal reflux disease in addition to suppressing gastric acid secretion.